2013
DOI: 10.1190/geo2011-0061.1
|View full text |Cite
|
Sign up to set email alerts
|

Microseismicity-constrained discrete fracture network models for stimulated reservoir simulation

Abstract: The effectiveness of hydraulic fracture stimulation in low-permeability reservoirs was evaluated by mapping microseismic events related to rock fracturing. The geometry of stage by stage event point sets were used to infer fracture orientation, particularly in the case where events line up along an azimuth, or have a planar distribution in three dimensions. Locations of microseismic events may have a higher degree of uncertainty when there is a low signal-to-noise ratio (either due to low magnitude or to propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Previous sensitivity studies have considered the effect on fracture volume, aperture and porosity when changing fracture length [25]; the effect on complexity of the fracture network when altering cohesion, the in-situ stress ratio, internal friction angle and injection rate [26,27] and the effect on the lateral respect distance (the lateral distance from a known fault that hydraulic fracturing should occur in order not to reactivate the fault) for different fracture intensities [19]. This paper adds to these investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous sensitivity studies have considered the effect on fracture volume, aperture and porosity when changing fracture length [25]; the effect on complexity of the fracture network when altering cohesion, the in-situ stress ratio, internal friction angle and injection rate [26,27] and the effect on the lateral respect distance (the lateral distance from a known fault that hydraulic fracturing should occur in order not to reactivate the fault) for different fracture intensities [19]. This paper adds to these investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity studies have investigated whether the total fracture volume, aperture, and porosity are sensitive to the fracture length [25] and the effect that cohesion, the in situ-stress ratio, the internal friction angle [26] and injection rate [26,27] have on the natural fractures. It was found that the total fracture volume, aperture, and porosity are not sensitive to the fracture length.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical interference can be demonstrated by experiments, eg, in Reference 42. Both analytical and numerical models of various degree of sophistication have been developed to model interference (43)(44)(45) A discrete element formulation (46) is capable of handling nonplanar fracture growth, toughness, and viscosity-controlled propagation regimes, and even the situation where fluid pressure is not sufficient to drive the fluid into the newly developed fracture tip (fluid lag.) (Fracture network) Inspired by the real-time experience provided by diagnostics, considerable efforts have been focused on describing the evolution of fracture networks in heterogeneous environment.…”
Section: Modelsmentioning
confidence: 99%
“…if S/N is big enough, the inversion of source mechanism is applied to the seismic data to characterize the failure-plane orientation and slip for almost all the detected seismic traces. Williams-Stroud et al, 2013) represents the result of final processed events of a well. Events showed in the image are colored with respect to fracture stage and sized with respect to different relative energy.…”
Section: Microseismic Methodsmentioning
confidence: 99%